Membangun Kepemimpinan Kristen yang Efektif dalam Gereja - Sitiana, Sitiana; Sakoikoi, Rapapi; Topayung, Semuel Linggi (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
This study explores the personal competencies of Christian leaders in the church context. Using a qualitative approach through literature review, this research analyzes biblical texts and related literature to understand the values and principles underlying effective Christian leadership. The primary focus of this research is on the characteristics of leaders that reflect Christ’s teachings, such as humility, love, and integrity. Additionally, this study discusses the challenges faced by Christian leaders in serving the congregation and how they can overcome these obstacles through spiritual development and community building. The results are expected to provide insights into best practices in leadership, as well as recommendations to strengthen faith communities and enhance the effectiveness of church ministry. By understanding Christian leadership in depth, it is hoped that better leaders can emerge, capable of inspiring and empowering congregations in carrying out the church’s mission.